Structural barriers to refugee, asylum seeker and undocumented migrant healthcare access. Perceptions of Doctors of the World caseworkers in the UK - Zara Asif; Hanna Kienzler (Elsevier, 2022)
This article contributes new insights into how refugees, asylum seekers and undocumented migrants experience access to healthcare in the UK from both the perspective of caseworker volunteers and the assessment of policy regulations that influence such experiences. Drawing on material taken from qualitative interviews conducted with Doctors of the World caseworkers and Freedom of Information documents from NHS trusts, we reveal the various complexities faced by refugees, asylum seekers and undocumented migrants when trying to access vital health care. These issues include, charging regulations, the refusal to register patients at GP practices without proof of ID, language barriers and complications navigating the healthcare system. We found that such deterrents lead to risky help and health seeking, lack of or inadequate healthcare, and worse health outcomes among these populations. DOTW caseworkers perceived policies such as charging regulations, to be unjust as they plunge patients into significant debt, which is reported to the Home Office and can lead to the detainment or deportation of patients and their families. Study participants called on the UK government to recognise health as a fundamental human right, to develop inclusive social policy and to create an empathetic health system that allows refugees, asylum seekers and undocumented migrants equitable access to health and social services. To achieve health for all, they argued the need for clearer guidelines regarding access to healthcare and charging regulations, with some suggesting the importance of revising current Department of Health and Social Care policies and Home Office measures. Our article concludes that there is a need to tackle the underlying causes of ill health, including discriminatory policies, racism, and exclusion; addressing the social and economic determinants of health; and providing meaningful and culturally sensitive healthcare and social support.